2021
DOI: 10.3390/ani11010234
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Medicine for Equine Musculoskeletal Diseases

Abstract: Musculoskeletal injuries and chronic degenerative diseases commonly affect both athletic and sedentary horses and can entail the end of their athletic careers. The ensuing repair processes frequently do not yield fully functional regeneration of the injured tissues but biomechanically inferior scar or replacement tissue, causing high reinjury rates, degenerative disease progression and chronic morbidity. Regenerative medicine is an emerging, rapidly evolving branch of translational medicine that aims to replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 344 publications
(557 reference statements)
0
34
0
Order By: Relevance
“…Superficial digital flexor tendon (SDFT) injuries are a severe problem that affect a large percentage of athletic and pleasure horses; often they develop recidivisms and, in the worst scenario, have to retire from competition early (9,47). In a One Health perspective, the equine could play an important role as a model for human musculoskeletal disorders because of their similarities (48)(49)(50), especially for investigating the regenerative efficacies of innovative treatments such as PRP, bone marrow aspirate (BMA), or MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Superficial digital flexor tendon (SDFT) injuries are a severe problem that affect a large percentage of athletic and pleasure horses; often they develop recidivisms and, in the worst scenario, have to retire from competition early (9,47). In a One Health perspective, the equine could play an important role as a model for human musculoskeletal disorders because of their similarities (48)(49)(50), especially for investigating the regenerative efficacies of innovative treatments such as PRP, bone marrow aspirate (BMA), or MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Tendinopathies are one of the most common orthopedic disorders in equine and human athletes, leading to lameness and pain (1)(2)(3)(4)(5). Tendon injuries are responsible for approximately one third of traumas that occur during the sporting career of horses (6,7), forcing a significant number of individuals to an early retirement from competition (8,9). The superficial digital flexor tendon (SDFT) is frequently injured in show jumping discipline due to the repeated and excessive loading forces that the tendon has to sustain after jumping and landing (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…McIlwraith et al reported the direct and indirect medical costs associated with OA to be between $3000–15,000 per horse each year in the U.S. alone [ 5 ]. Specific populations of horses may also suffer from higher rates of OA, with up to 66% of Thoroughbred racehorses developing this disorder, resulting in pain and significantly shortened career-spans [ 6 , 7 ].…”
Section: Osteoarthritis: General Reviewmentioning
confidence: 99%